47.6k views
2 votes
Select the correct answer from each drop down menuThere is options

Select the correct answer from each drop down menuThere is options-example-1
User Dxb
by
4.4k points

1 Answer

3 votes

ANSWER:


\begin{equation*} 4x^5-16x^3+x^2-4 \end{equation*}

Step-by-step explanation:

Given:


\begin{gathered} f(x)=0.5^2-2 \\ \\ g(x)=8x^3+2 \end{gathered}

We can go ahead and determine (f * g)(x) as seen below;


\begin{gathered} (f\cdot g)(x) \\ \\ =f(x)\cdot g(x) \\ \\ =(0.5^2x-2)(8x^3+2) \\ \\ =0.5x^2(8x^3)+0.5x^2(2)-2(8x^3)-2(2) \\ \\ =4x^5+x^2-16x^3-4 \\ \\ =4x^5-16x^3+x^2-4 \end{gathered}

User Pierre Clocher
by
5.6k points